IMPACT OF NATIONAL CULTURE ON PUPILS PISA RESULTS: THE CASE OF EUROPEAN COUNTRIES - CHLEBOUNOVÁ, Denisa; ODEI, Samuel Amponsah (Studia Universitatis Babeș-Bolyai Negotia, 2019)
Objective: This paper aims at finding out whether the national cultural dimensions affect the quality of European education systems. The research question therefore focuses on whether and how large is the impact of national cultural dimensions on pupils' results measured by PISA results. Methodology: We used data on the national cultural dimensions from the GLOBE project and we used the PISA results for pupils' results. We did Structural Equation Model (SEM) for our empirical analysis. This model was preferred because it helped to establish the causal relationship between the cultural dimensions and pupil’s performance. Results: Our results have demonstrated that: pupils' performance are influenced by some national cultural dimensions. PISA results correlate negatively with the cultural dimension values of Uncertainty Avoidance and Future Orientation, on the other hand PISA results positively correlate with performance Orientation values and Assertiveness values. Implication: This research presents and elucidates significant cultural factors that affect pupils' results. It gives an impulse to understanding the cultural formulas that apply in the learning process. This knowledge allows for the appropriate and timely implementation of effective learning methods that have a positive impact on pupils' results. JEL Code: I21, I24, I29